Idiopathic Infantile Arterial Calcification: A Possible Cause of Refractory Cardiopulmonary Failure in Infancy - A. Nael; P. J. Siaghani; D. Chen; S. G. Romansky; L. Shane (Case Reports in Pathology)
Idiopathic Infantile Arterial Calcification is a rare autosome recessive disease characterized by extensive calcification of medium and large arteries. Loss-of-function mutations in ectonucleotide pyrophosphatase/phosphodiesterase 1 gene have been described in more than 80% of the cases. Although the diagnosis is usually made at autopsy, it is possible to identify cases based on clinical presentation, radiology findings, and molecular studies. Appropriate treatment can be initiated and has been shown to successfully induce permanent remission. We report a 4-week-old neonate who initially presented with respiratory distress, heart failure, and Coxsackie B viremia suggestive of viral induced cardiomyopathy. His symptoms progressed to multiple organ failure and he eventually expired at four weeks of age. On autopsy, diffuse calcium deposition within the internal elastic lamina of medium and large arteries was identified, as well as narrowing of lumen due to myointimal proliferation. This case report will emphasize the importance of taking this rare curable disease into consideration in all cases of infants with cardiopulmonary failure.